Diverse pathways in becoming an adult: The role of structure, agency and context. (December 2016) - Schoon, Ingrid; Lyons-Amos, Mark
Highlights: Current debates on youth transitions are dominated by a dualistic view of optimal versus problematic pathways which does not capture the complexity of young people's experiences. We introduce a diverse pathways view that enables a more holistic understanding of youth transitions and a move towards a more fine graded understanding of social inequalities in the transition from school to work. Using sequence analysis we assess changes in the timing and sequencing of early education and employment transition among two age cohorts born between 1980 and 1989. We identify five distinct pathways which are shaped by individual agency as well as structural variables, including regional youth unemployment. Abstract: Although the transition from education to work has been a topic of much research, there is still lack of understanding regarding experiences of recent cohorts of young people. Moreover, much of the debate has focused on the polarization of youth transitions, at the neglect of a large group of young people who fall outside this dualism. This paper introduces a diverse pathways view offering a more comprehensive understanding of changing youth transitions and examines how transitions are shaped by interactions between structure and individual agency. The study is based on data from the British Household Panel Study (BHPS) and the UK Household Longitudinal Study (UK-HLS) using sequence analysis to identify transition patterns among cohorts born in 1980–1984 and 1985–1989. Five distinct clusters could be identified, differentiating between those who participate in extended education, two pathways dominated by continuous employment, either directly after completing compulsory schooling at age 16 or after some further education, and two pathways characterized by exclusion from the labor market (either through prolonged experience of unemployment or inactivity). Both structural and agency variables are associated with variations in transition patterns, pointing to the need of conceptualizing the role of the agent as well as that of structures and resources for a better understanding of the processes underlying the selection into different pathways.